Two new species of Thlaspidula Spaeth, 1901 (Coleoptera: Chrysomelidae: Cassidinae) from Sulawesi - Budi, Anang Setyo; Świętojańska, Jolanta (Zootaxa, 2025)
Two new for science species of the genus Thlaspidula Spaeth, 1901 are described and illustrated from Sulawesi, Indonesia. Thlaspidula gandangdewata, sp. nov. is described based on specimens collected from Mount Gandangdewata whereas Thlaspidula sarinoi, sp. nov. on material from Mount Torompupu. Photographs of the habitus and illustrations of diagnostic characters are presented. Key to all members of the genus Thlaspidula is given.